PROMOTING ARABIC VOCABULARY PUBLIC HEALTH-BASED FOR ARABIC TEACHING MATERIALS - Moh. Buny Andaru Bahy; Kamal Yusuf (International Conference on Social and Islamic Studies, 2021)
The emergence of new vocabulary related to public health is very important for the public toknow, especially the new vocabulary about the Covid-19 pandemic in Arabic. This studyaims to promote Arabic vocabulary - based teaching materials related to public health withthe aim of introducing Arabic learners to new vocabulary . This study uses a descriptivequalitative approach based on library research by using the steps of preparing teachingmaterials using the Dick and Carey model. The data for this research is sourced from theonline electronic media of the BBC Arabic, using vocabulary adaptation techniques tocompile Arabic teaching materials. The results of this study confirm that in the preparation ofArabic teaching materials, the four basic principles of foreign language learning approach areused. Based on the research that has been carried out, it was found that there are a number ofnew vocabulary related to the Covid-19 pandemic in Arabic. Furthermore, the adaptation ofthe development of new Arabic vocabulary teaching materials is arranged according to theprinciples and concepts of language learning, so that in the implementation and teaching ofnew vocabulary students are expected to achieve maximum results.